Analisis Perbandingan Pengeluaran dan Penghasilan Pedagang Pasar Sukaramai & MMTC dengan Para Penjual Kaki Lima yang Berada Dikawasan Universitas Negeri Medan - Putri Maulidina Fadilah; Sudianto Manullang; Angelica Carolina Tambunan; Hanafi Irsyad Pulungan; Lirana Sapriani Gulo; Naomi Febrina Sitompul (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine and compare the expenditure and income patterns between traditional market traders in Sukaramai Market and MMTC with street vendors operating around the State University of Medan (UNIMED). This study is based on the main differences between the two groups, especially related to business legality, sales location, and operational costs, which have the potential to affect business effectiveness and the economic welfare of the actors. The comparative quantitative method was used to collect data through questionnaires and Simple Random Sampling sampling techniques on 45 respondents, consisting of 30 market traders and 15 street vendors. The collected data were then analyzed using statistical inference techniques to obtain accurate and reliable parameter estimates. The results of the study show that market traders have an average income of IDR 9.37 million with expenses of IDR 6.7 million per month, so that the net profit obtained reaches IDR 2.67 million. Meanwhile, street vendors have an average income of IDR 7.2 million and expenses of IDR 5.53 million, so that their net profit is around IDR 1.67 million. Although market traders' expenses are higher, they still get a greater net profit. This study confirms that business location, legality, and management system factors significantly affect the efficiency and economic success of traders. This finding is very relevant as a basis for formulating fair and sustainable policies for empowering the informal sector, especially for small and micro traders in urban areas, in order to optimally improve their economic welfare.